PENERAPAN KONSEP TA'DIB NAQUIB AL-ATTAS DALAM PENDIDIKAN KELUARGA DI ERA SOCIETY 5.0 - Yanti, Yanti; Aida Hayani (Fakultas Tarbiyah IAI Almuslim Aceh, 2023)
In facing the dynamics of social change in the era of Society 5.0, family education plays a crucial role in shaping the character and moral values of the next generation. In Islam, the concept of ta'dib (education) holds a central role in shaping a good and virtuous personality. In the present modern era, technological advancements and social changes have introduced new challenges in raising children with proper etiquette. The cultivation of etiquette should be initiated as early as possible because the development of etiquette in children is more conducive during their formative years than when they have matured into adulthood. Naquib Al-Attas is a prominent Muslim scholar who has developed the concept of ta'dib (education or nurturing) as a fundamental pillar in Islamic understanding regarding the formation of good ethics and morals in a Muslim individual. The methodology employed in this research involves a literature review and analysis of scholarly references related to the concept of ta'dib according to Naquib Al-Attas and its application within the family. The objective of this research is to explore and elaborate on the concept of ta'dib and its implementation in the family from the perspective of Naquib Al-Attas.